EP1164 Modified oblique versus classical 'lazy S' incision for inguino-femoral lymph node dissection; complications, node count and hospital stay. (1st November 2019) - Jones, S; Davies, J; Jones, R; Lim, K; Howells, R; Sharma, A
Abstract : Introduction/Background: Inguino-femoral lymph node dissection plays a crucial role in the management of vulval cancer. The procedure is associated with high complication rates including infection, lymphocysts and wound dehiscence. Several skin incision techniques exist and practice amongst gynaecology oncologists is variable. Little evidence exists to guide surgeons regarding optimal surgical approach. This study aimed to determine the difference in complication rates, node harvest and length of stay between patients undergoing the modified oblique and classical 'lazy S' skin incision. Methodology: A retrospective review of 4 years of data between 2014 and 2018 was carried out in the UHW, Cardiff. Data collected included age, BMI, incision, length of stay, complications, cancer stage, suture material, node count and recurrence of disease. Data were analysed using SPSS software and clinical significant was set as p≤0.05. Results: Thirty-five cases of classical 'lazy S' and 14 cases of modified oblique. More serious, grade 3/4 complications were significantly more common following classical 'Lazy S' versus modified oblique (20/35, 57.1% vs. 2/14, 14.3%). Mean number of nodes harvested was significantly higher in the classical 'Lazy S' group compared to the modified oblique (11.1 vs. 7 nodes). Mean hospital stay was significantly higher in patients undergoing classical 'Lazy S' vs. Modified oblique (10.7 vs. 4.5 days). One case of groin node recurrence occurred and this patient was in the classical 'lazy S' arm. Conclusion: This study demonstrates significantly lower rates of overall and serious complications following modified oblique skin incision compared to classical 'Lazy S'. However, this would appear to be at the compromise of a reduced node count. This study was not designed to determine the clinical significance of node count and recurrence but this is also a subject upon which the literature is scarce. More research is required to determine optimal surgical incision in this challenging procedure. Disclosure: Nothing to disclose